Interfacial integrity of bonded restorations with self-etching adhesives: Water storage and thermo-mechanical cycling - Martins, Gislaine Cristine; Sánchez-Ayala, Alfonso; D’Alpino, Paulo Henrique Perlatti; Calixto, Abraham Lincoln; Gomes, João Carlos; Gomes, Osnara Maria Mongruel (European Journal of Dentistry, 2012)
Objectives: Objective: To evaluate the effect of thermo-mechanical cycling (TMC) on the microleakage (μL) and axial gap width (AG) of Class V bonded restorations in premolars using self-etching adhesive systems. The bond strength of composite restorations to dentin (μTBS) using the same adhesives was also evaluated in third molars after water storage: 24 h and 6 months. The research hypotheses were tested for the results of two self-etching adhesives in comparison when a conventional two-step adhesive was used: (1) the μL and AG would be lower, regardless of TMC; (2) the μTBS of self-etching adhesives would be higher, irrespective of evaluation times.Methods: Sixty Class V composite restorations were made in 30 premolars and bonded with Adper Single Bond 2 (ASB2), AdheSE (ASE), and Adper Prompt L-Pop (APL-P) (n=20). Dentin μL and AG were immediately measured for half of the sample. The other half was evaluated after TMC. Eighteen third molars were also selected and bonded using the same adhesives to test the μTBS to dentin. Specimens were evaluated after 24 h and 6 months of water storage.Results: No differences in μL and AG were found among the groups (P>.05). The μTBS mean values were: ASB2>ASE>APL-P (P<.05); only Adper Single Bond 2 presented a significantly lower μTBS after water storage (P<.05)Conclusions: The bonding approach does not influence the microleakage and interfacial gap extension. Despite the decrease in the mean values, the bond strength to dentin of the conventional, two-step adhesive remains high after 6 months of water storage. (Eur J Dent 2012;6:169-177)
Keywords: Dentin-bonding agents; bond strength; durability; microleakage